Introduction to Physical Oceanography - Stewart, Robert H. (Open textbook library., 2008)
This textbook covers physical-oceanographic processes, theories, data, and measurements, targeted at upper-division undergraduates and graduate students in oceanography, meteorology, and ocean engineering. In addition to the classical topics, the author includes discussions of heat fluxes, the role of the ocean in climate, the deep circulation, equatorial processes including El Nino, data bases used by oceanographers, the role of satellites and data from space, ship-based measurements, and the importance of vorticity in understanding oceanic flows. Students should have studied differential equations and introductory college physics, although math is de-emphasized.